2005
DOI: 10.1016/j.dmr.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Readiness and Training Needs of Non-urban Physicians in Public Health Emergency and Response

Abstract: Emergency readiness has become a public health priority for United States communities after the 9/11 attacks. Communities that have a less developed public health infrastructure are challenged to organize preparedness and response efforts and to ensure that health care providers are capable of caring for victims of terrorist acts. A survey was used to assess nonurban physicians' prior experience with and selfconfidence in treating, and preferred training needs for responding to chemical, biologic, radiologic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
5
23
0
Order By: Relevance
“…This reflects Jordanian RNs' concern and recognition about the importance of disaster preparedness. These finding are consistent with the results of Hsu et al (2005) who found that emergency preparedness is a public health priority for all health care providers.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…This reflects Jordanian RNs' concern and recognition about the importance of disaster preparedness. These finding are consistent with the results of Hsu et al (2005) who found that emergency preparedness is a public health priority for all health care providers.…”
Section: Discussionsupporting
confidence: 95%
“…Moreover, it is also not documented to what extent RNs learned about disaster plans in their workplace. These findings are congruent with findings by Hsu et al (2005), who found that the majority (72.4%) of their respondents reported that they had not participated in disaster preparedness and response training. In addition, knowing in advance exactly what is expected of RNs will provide RNs with an opportunity to acquire the pertinent knowledge and to practice necessary skills beforehand.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this survey provide some insight into the current state of perceived pandemic preparedness among a cohort of GPs in one part of the United Kingdom. Internationally, support for our results is provided by studies examining GPs' views regarding their role and practice preparedness in responding to public health emergencies in general including SARS and other biothreats such as pandemic influenza [4][5][6][7][8]. As with this study, respondents highlighted risk communication, clarity of roles, appropriate resources as well as targeted education and training as areas that needed to be addressed in order to be better prepared for a major public health emergency.…”
Section: Discussionmentioning
confidence: 86%
“…Internationally, research has been conducted on GP preparedness for public health emergencies such as bioterrorism, natural disasters and severe acute respiratory syndrome (SARS) [4][5][6][7][8]. To our knowledge there are no published surveys specifically examining GP preparedness for an influenza pandemic or GP preparedness in non-urban areas.…”
Section: Introductionmentioning
confidence: 99%